REPRESENTASI BUDAYA MISTIS DALAM TUTURAN FILM WAKTU MAGRIB: KAJIAN ANTROPOLINGUISTIK - Nadirawati, Anggun Salsabila; Adhisty Dwiriyani Putri (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research explores the representation of mystical culture in the film Waktu Magrib through an anthropolinguistic approach. Javanese society holds strong beliefs in mystical elements such as spirits, sacred objects, and magical times like dusk. This study aims to describe how mystical beliefs are expressed in the dialog and scenes of the film, especially regarding objects (amulets, stones), places (forests, rivers), and times (sunset). Using a qualitative descriptive method and content analysis, the researcher examines dialogues and visual cues as data sources. The results show that the film reflects mystical values embedded in Javanese oral traditions, such as warnings not to play during sunset or the use of amulets for protection. These representations serve as both cultural memory and means of transmitting traditional wisdom. Language plays a central role in embodying and preserving these mystical elements, acting as a vehicle for spiritual knowledge. The study concludes that films, as popular cultural products, can effectively represent and sustain traditional values in a symbolic, accessible form for modern audiences